Determination of Surface Drainage Coefficient through Rainfall Analysis for North Lakhimpur (Assam) - P. P. Dabral; Neelakshi Baithuri (Journal of Soil and Water Conservation, 2022)
In this study the drainage coefficient for North Lakhimpur (Assam) was estimated. From 24 years daily rainfall data (1981 -2004), year wise one to seven consecutive days maximum rainfall was obtained. Three commonly used distribution functions ( viz normal, Log normal and Gamma) were fitted. From the best fitted functions one to seven consecutive days rainfall values for 2, 5, 10 and 20 years recurrence interval (R.I.) was determined. The drainage coefficients were calculated by subtracting basic infiltration rate from consecutive days maximum rainfall for R.I. of 2, 5, 10 and 20 years. Study revels that the soil of North Lakhimpur(Assam) having predominantly loamy to clay loam and having basic infiltration rate between 1 to5 mm/hr may necessarily have to be provided with agricultural land drainage for its major crops grown in the area.